PREPARING STUDENT YOUTH FOR ENTREPRENEURIAL ACTIVITY: RESULTS OF THE EXPERIMENT (Innovative professional education, 2022)
The results of the experimental verification of the effectiveness of organizational and pedagogical conditions for the formation of the readiness of future skilled workers for entrepreneurial activity are analyzed. It was found that after the introduction of these conditions in the students of the experimental groups there were significant positive changes to increase the level of readiness for entrepreneurship.
Keywords: students; vocational education institution; readiness for entrepreneurial activity; experimental testing; organizational and pedagogical conditions